Leading in sync : teacher leaders and principals working together for student learning - Berg, Jill Harrison (ASCD, 2018)
This book encourages educators and administrators to examine their own thinking about what constitutes high-quality teaching so they can work toward a shared vision, identify teachers' many strengths as potential assets for achieving the shared vision, recognize ways in which most teachers are already leading, support leadership collaboration through efficient, effective communication, and develop the trust required to learn to lead together.